Transformasi Konsep Kepemilikan Harta Dalam Hukum Bisnis dan Konteks Sejarahnya - Saefullah, Saefullah (JURNAL USM LAW REVIEW, 2024)
This study aims to explore the transformation of the concept of property ownership in business law as a reflection of adaptation to social, cultural, and economic changes. The complex dynamics in the relationships among individuals, companies, and the state regarding personal ownership rights, collective rights, and legal norms are highlighted. The urgency of this research lies in understanding the evolution of the relationship between law and business history, where property is not only an object of ownership but also a business asset. This research distinguishes itself from previous studies by focusing on the transformation of the concept of property ownership in business law and its historical perspective. The research employs a doctrinal method with a literature review as a secondary data source. The innovative contribution of this research includes a profound understanding of ownership theory perspectives, encompassing concepts of individual ownership rights, collective rights, and moral and ethical dimensions. The transformation of the concept of property ownership in Indonesia is reflected in its history, influenced by colonial law and local values. The impacts of globalization, technology, and social changes have led to a shift in perspectives on property ownership. Business law and property ownership are intertwined, regulating business activities with regulations reflecting Islamic law, civil law, and business law perspectives. The conclusion emphasizes the importance of a deep understanding of the transformation of the concept of property ownership to meet societal demands and ensure the sustainability of legal business relationships.Penelitian ini bertujuan untuk menggali transformasi konsep kepemilikan harta dalam hukum bisnis sebagai refleksi adaptasi terhadap perubahan sosial, budaya, dan ekonomi. Terdapatnya dinamika kompleks dalam hubungan individu, perusahaan, dan negara terkait hak milik pribadi, hak kolektif, dan norma hukumnya. Urgensi penelitian ini terletak pada pemahaman evolusi hubungan antara hukum dan sejarah bisnis, dengan harta bukan hanya sebagai objek kepemilikan tetapi juga sebagai objek bisnis. Metode penelitian yang digunakan adalah metode doktrinal dengan studi kepustakaan sebagai sumber data sekunder. Kontribusi kebaharuan penelitian ini mencakup pemahaman mendalam terhadap pandangan teori kepemilikan, termasuk konsep hak milik individu, hak kolektif, dan dimensi moral dan etika. Transformasi konsep kepemilikan harta di Indonesia tercermin dalam sejarahnya, dipengaruhi oleh hukum kolonial dan nilai-nilai lokal. Dampak globalisasi, teknologi, dan perubahan sosial menciptakan pergeseran dalam cara pandang terhadap kepemilikan harta. Hukum bisnis dan kepemilikan harta saling terkait, mengatur aktivitas bisnis dengan regulasi yang mencerminkan pandangan hukum Islam, hukum perdata, dan hukum bisnis. Kesimpulan menekankan pentingnya pemahaman mendalam terhadap transformasi konsep kepemilikan harta untuk menjawab tuntutan masyarakat dan memastikan keberlanjutan hubungan hukum-bisnis.